INTRAVENOUS INFUSION DOSING SYSTEM FOR VOLUME CONTROL BASED ON SIGNAL PERIODIC MEASUREMENT - Lazuardi Umar; Vira Annisa Rosandi; Rahmondia Nanda Setiadi; Zulharman Zulharman (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Intravenous fluid therapy is a commonly used treatment modality that is used in the treatment of hospitalized patients. Intravenous flow rates are often controlled by counting the number of fluid drops in a drip chamber while adjusting the intravenous line with a watch. In this research, an intravenous infusion dosing system was designed based on periodic signal measurement using a pair of light couplers consisting of a transmitter and a receiver. The transmitter is built using an infrared LED (BPV10NF), while the receiver uses an infrared photodiode detector (BPW34). The infusion droplet will pass a slit between the two coupler components and interrupt the light transmission from the transmitter to the receiver, which will affect the current through the photodiode and change the output status of the circuits. The parameters obtained from this circuit signal are droplet frequency from 1 Hz to 10 Hz and droplet sizes 0.05 ml and 0.0167 ml. The resulting output signal is in the form of pulses due to the interruption of the droplet when it passes through the optocoupler. The droplet frequency is calculated based on the period between adjacent droplets, while the droplet size can be measured based on the width of the resulting pulse. For the droplet measurement process, variations of the droplet period and the number of droplets per ml were carried out. The droplet period is regulated by manually adjusting the aperture of the infusion droplet outlet faucet. In contrast, the droplet size is controlled by two types of infusion devices with 20 drops/ml and 60 drops/ml specifications. The experimental results can be used to develop a system response that detects changes in period and droplet size.